El maestro (San José, C.R. : UNED, 2002)
Presenta aspectos relevantes sobre el papel de don Uladislao Gámez Solano, en la educación costarricense
Keywords: VIDEOGRABACIONES; GAMEZ SOLANO, ULADISLAO, 1909-2005; DOCENTES